Irish Costume and the Construction of Anglo-Irish Identity - Edwards, Alicia (Revue YOUR Review (York Online Undergraduate Research), 2017)
This project relies on select theories of identity formation (e.g., Benedict Anderson’s “imagined communities”; Judith Butler’s “gender performativity”) in order to better understand how “Celticness” is [re]produced in numerous cultural artifacts. This interdisciplinary project examines fashion, mediaeval bridal costume, Celtic knots, and representations of the shamrock in the Anglo-Irish culture in order to understand how specific images become complex signs of Celtic Identity, from the Celtic Revival Period to the present. Gaps in scholarship are suggested.